Revealing Growth Perspectives: A Strategic Business Plan for MJH Enterprise's in the Halal Organic Chicken Supply Industry: Investigating Strategies for Expanding Market Presence in Medium-Sized Supermarkets in Batu Pahat - Ab Rahman, Nurul Ammirah; Ali, Maimunah (Research in Management of Technology and Business, 2023)
Chicken business suppliers in Malaysia have become a lucrative industry due to the increasing demand for chicken meat. The COVID-19 pandemic has led to a need for food quality, safety, and health options in the chicken meat supply chain. Muslim consumers look for meat that is fresh, natural and simple to digest, halal and produced using hygienic tools in a clean environment. MJH Enterprise, a Muslim Bumiputera-established business, processes chicken meat from livestock into fresh and frozen organic chicken. Located in Batu Pahat, Johor, MJH targets consumers in Malaysia and currently, has a capacity of approximately 18,000 little chickens per cycle twice a year. The company follows HALAL certification requirements and focuses on producing fresh products for the domestic market. MJH emphasizes quality products and sustainability by packing chicken meat in proper packages to maintain freshness. The company aims to expand its organic chicken product distribution by promoting the product to established supermarkets in Batu Pahat.